Military Industrial Complex and National Security in Nigeria, 2015 – 2022 - Akinga, Anna Yonnana; Okorie, Isaac Chukwueuka (NIU Journal of Humanities, 2023)
The ability to wage and win a war or to deter potential adversaries depends on the degree of technological wealth in the country, which should be seen to be adequately developed and functional. Therefore, the success of modern day military forces is measured by their ability to develop and use unique technologies to effectively confront unique security challenges this entails the importance of military industries and technological development to the national security of any country. This study, therefore, sets out to discuss the relevance of Military Industrial Complex (MIC) in relation to the national security in Nigeria between 2015 and 2022. This study adopts the use of secondary source as its methodology, which will be accessed through published works, journal articles, internet sources and other secondary source materials. Some of the findings of this study are as follows; 1) Military Industrial Complex (MIC) began to be firmly established after the WW II. 2) a country’s maintenance of a good national security is not unconnected with its ability to produce and develop a high level of local military arms and ammunitions through its MIC. 3) Nigeria’s overdependence in arms and ammunitions’ importation is affecting both her national security and economy. 4) between 2015 and 2022, Nigeria has spent more money importing military hardware. 5) the MIC in Nigeria is lagging behind other MICs even in some Third World countries like Brazil, India and South Africa, hence the need for its rehabilitation, upgrade and reinvestment. The study concludes that for Nigeria’s national security and economy to be better, the government ought to invest more in the development of a viable and strong MIC to drastically reduce her high dependence on foreign countries for her national security. Keywords: MIC, National Security, Nigeria, Technological Development, Third World Countries